Feeding in the fields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Veld Management in South Africa. N Tainton. University of Natal Press. 1999. 492 pp. ISBN 0 86980 948 2 CTA number 968. 80 credit points. ZAR 275 44 University of Natal Press Private Bag X01 Scottsville 3209, South Africa Fax: +27 331 260 5